2020
DOI: 10.3390/microorganisms8091280
|View full text |Cite
|
Sign up to set email alerts
|

Recent Molecular Evolution of Human Metapneumovirus (HMPV): Subdivision of HMPV A2b Strains

Abstract: Human metapneumovirus (HMPV) is a major etiological agent of acute respiratory infections in humans. HMPV has been circulating worldwide for more than six decades and is currently divided into five agreed-upon subtypes: A1, A2a, A2b, B1, and B2. Recently, the novel HMPV subtypes A2c, A2b1, and A2b2 have been proposed. However, the phylogenetic and evolutionary relationships between these recently proposed HMPV subtypes are unclear. Here, we report a genome-wide phylogenetic and evolutionary analysis of 161 HMP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
32
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(35 citation statements)
references
References 39 publications
3
32
0
Order By: Relevance
“…The tree was reconstructed using the GTR +G +I substitution model with 1000 bootstraps. Fourteen complete F gene sequences (thirteen from GenBank, indicated with accession numbers, and one from [10]) were included for the tree topology. Viruses sequenced in this study that contain a 111nucleotide duplication in the G gene that was confirmed by Sanger sequencing of the G gene are underlined.…”
Section: Ethical Statementmentioning
confidence: 99%
“…The tree was reconstructed using the GTR +G +I substitution model with 1000 bootstraps. Fourteen complete F gene sequences (thirteen from GenBank, indicated with accession numbers, and one from [10]) were included for the tree topology. Viruses sequenced in this study that contain a 111nucleotide duplication in the G gene that was confirmed by Sanger sequencing of the G gene are underlined.…”
Section: Ethical Statementmentioning
confidence: 99%
“…Worldwide, the hMPV prevalence in hospital inpatient and community studies, in children and the elderly, varies from 1.7 to 17%, with a higher prevalence in outpatients compared to inpatients, and in children < 5 years of age compared to older age groups [ 29 , 33 , 34 ], as in other parts of China [ 4 , 10 ]. In this study, 1133 children with severe acute respiratory tract infection in Huzhou from 2016 to 2020 were tested for hMPV RNA, and 56 (4.94%) were positive (negative for other pathogens), indicating that hMPV is an important respiratory pathogen among children in Huzhou.…”
Section: Discussionmentioning
confidence: 99%
“…Analysis of hMPV genetic lineages identifies two genotypes, A and B (Peret et al, 2002; van den Hoogen et al, 2004). The genotypes are further divided into 5 subgroups (A1, A2a, A2b, B1 and B2) primarily based upon the attachment protein sequence variability (Nao et al, 2020; van den Hoogen et al, 2004; Yang et al, 2013). hMPV has a seasonality of winter and early spring with co-circulation of the two genotypes frequently observed (Kahn, 2006).…”
Section: Introductionmentioning
confidence: 99%